Synthesis and characterization of Nd-Fe-B based magnetic nanomaterials - Pratap Kumar Deheri. (2012)
Modern high energy product permanent magnets are based on nanostructured magnetic materials. The improved magnetic properties of these magnetic materials are determined to a great extent by the alloy composition, phases present and crystal size. Therefore the development of nanocrystalline magnetic materials requires the study of synthesis techniques, crystal structure as well as phase transformation mechanisms. The main objectives of this project are the synthesis, characterization and property evaluation of Nd-Fe-B based magnetic nanostructures. Nd-Fe-B based magnetic nanostructures were synthesized by NaBH4 reduction, sol-gel method and melt spinning techniques. Sol-gel followed by reduction diffusion was found to be a successful method to synthesize Nd2Fe14B magnetic nanoparticles. The mechanism of formation was studied. The magnetic properties, phase analysis and microstructural investigations were performed by Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance (NMR), vibrating sample magnetometry (VSM), X-ray diffraction (XRD), neutron powder diffraction (NPD), field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) techniques. Nd-Fe-B based magnetic nanomaterials were successfully synthesized by a combination of the sol-gel technique followed by the reduction diffusion method. Nd-Fe-B gel was prepared from the chloride salts of Nd, Fe and H3BO3 using citric acid and ethylene glycol as the gelating agent. Annealing of the gel at 800 °C resulted in the formation of the Nd2O3, NdFeO3, Fe2O3 and B2O3 phases. Reduction of this oxide mixture by CaH2 resulted in the successful formation of the Nd2Fe14B and α Fe nanoparticles. The magnetic interactions were calculated by the Henkel plot, the as-synthesized powder was found to be exchange coupled, the removal of CaO led to dipolar interactions and lower remanent magnetization.